FATS OF INSECTS V SAN LUIS POTOSIHENARIUM PURPURASCENS CHARPENTIER - GIRAL, FRANCISCO (Laboratoria Centro Investigaciones Industria Nacional Quim-Pharm, CD MEXICO, DF, MEX, 1963)
The total lipid of the Mexican orthopteran M atlanis was fractionated and the components characterized The outstanding features are the preponderance of stearic over palmitic acid and the high proportion of the C20 acids in the unsaturated fraction The
J ANIM SCI
Keywords: FATS, INSECTS, SPHENARIUM PURPURASCENS CHARPENTIER; CIENCIAS DE LA VIDA; BIOLOGIA MOLECULAR; BIOLOGIA MOLECULAR DE PLANTAS